Role of Religious Sponsors in Development of Holistic Secondary School Students in Nyeri County - Kagema, Peterson Githinji (Analisa: Journal of Social Science and Religion, 2021)
Historically, religious sponsors have played a significant role in promoting holistic growth of students through emphasizing Christian based values in learning institutions. This have been showed by ever increasing seasonal social, moral, and ethical challenges facing students which include early pregnancies among female students, drugs and substance abuse, religious radicalization, burying, arson, among others. However, there has been a great concern from the public discourse on the laxity of the church as religious sponsors in schools from the frequent moral decay displayed by the students today. This article assesses the role of religious sponsors in development of holistic secondary school students in Nyeri County, Kenya. This study adopts a descriptive approach through collecting primary data from 68 CU/CA patrons, 99 students and 68 school administration. This article confirmed that various religious sponsors promote students' moral, social and spiritual development to students through organizing frequent prayer sessions, Biblical expositions, as well as offering Christian based guidance and counseling. However, this have not been to the maximum as could be expected in religious contexts. This study recommends for revitalized pastoral reforms from both the schools and the church. This will ensure that secondary schools fully utilize the rich valuable chaplaincy ministry based on pastoral care and counseling services as facilitated by the respective religious sponsors.